L-Arginine Affects Aerobic Capacity and Muscle Metabolism in MELAS (Mitochondrial Encephalomyopathy, Lactic Acidosis and Stroke-Like Episodes) Syndrome. - Lance H Rodan; Greg D Wells; Laura Banks; Sara Thompson; Jane E Schneiderman; Ingrid Tein (PLoS ONE, 2015)
Objective To study the effects of L-arginine (L-Arg) on total body aerobic capacity and muscle metabolism as assessed by (31)Phosphorus Magnetic Resonance Spectroscopy ((31)P-MRS) in patients with MELAS (Mitochondrial Encephalomyopathy with Lactic Acidosis and Stroke-like episodes) syndrome. Methods We performed a case control study in 3 MELAS siblings (m.3243A>G tRNA(leu(UUR)) in MTTL1 gene) with different % blood mutant mtDNA to evaluate total body maximal aerobic capacity (VO(2peak)) using graded cycle ergometry and muscle metabolism using 31P-MRS. We then ran a clinical trial pilot study in MELAS sibs to assess response of these parameters to single dose and a 6-week steady-state trial of oral L-Arginine. Results At baseline (no L-Arg), MELAS had lower serum Arg (p = 0.001). On 3(1)P-MRS muscle at rest, MELAS subjects had increased phosphocreatine (PCr) (p = 0.05), decreased ATP (p = 0.018), and decreased intracellular Mg(2+) (p = 0.0002) when compared to matched controls. With L-arginine therapy, the following trends were noted in MELAS siblings on cycle ergometry: (1) increase in mean % maximum work at anaerobic threshold (AT) (2) increase in % maximum heart rate at AT (3) small increase in VO(2peak). On (31)P-MRS the following mean trends were noted: (1) A blunted decrease in pH after exercise (less acidosis) (2) increase in Pi/PCr ratio (ADP) suggesting increased work capacity (3) a faster half time of PCr recovery (marker of mitochondrial activity) following 5 minutes of moderate intensity exercise (4) increase in torque. Significance These results suggest an improvement in aerobic capacity and muscle metabolism in MELAS subjects in response to supplementation with L-Arg. Intramyocellular hypomagnesemia is a novel finding that warrants further study. Classification of evidence Class III evidence that L-arginine improves aerobic capacity and muscle metabolism in MELAS subjects. Trial registration ClinicalTrials.gov NCT01603446.